Семантические типы и композиционно-речевые особенности делового юридического письма (на материале английского языка) - Нижникова, Л. В.; Нижнікова, Лариса Вікторівна; Nizhnikova, L. V.; Доленко, Л. В.; Доленко, Людмила Василівна; Dolenko, L. V. (Одеса, 2016)
Статтю присвячено дослідженню англомовного ділового юридичного листа як різновиду офіційних ділових документів, які реалізують офіційно-діловий стиль із властивими йому загальними особливостями. У роботі розглядаються семантичні типи та композиційно-мовленнєві особливості юридичного листа.

The article is devoted to the investigation of business legal letter as a variety of official business documents, realizing official business style with general attributes characteristic of it. Semantic types and composition and speech peculiarities of business legal letter are considered in the work.
Нижникова Л. В. Семантические типы и композиционно-речевые особенности делового юридического письма (на материале английского языка) / Л. В. Нижникова, Л. В. Доленко // Одеський лінгвістичний вісник. – 2016. – Вип. 7. – С. 78-81.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; офіційно-діловий стиль; діловий юридичний лист; специфіка оформлення ділового юридичного листа; ділова мова; official and business style; business legal letter; specifics of legal registration of business letters; business speech